Paper 77: Only a Minority of Patients with Rotator Cuff Tear Achieve MCID for PROMIS Pain and Function Measures Following Initial Non-Operative Treatment. Issue 7 (30th July 2022) - Patel, Mit; McGee, Anna; Castle, Joshua; Elhage, Kareem; Lizzio, Vincent; Makhni, Eric; Keith, Katherine
Objectives: It is still unclear which patients benefit from nonoperative treatment of rotator cuff tear versus those who benefit from early intervention. The purpose of our study was to determine which patients benefit from conservative therapy and establish the MCID of patients undergoing nonoperative treatment for partial and full-thickness rotator cuff tears (RCT). Methods: We performed a retrospective cohort study evaluating non-operatively managed patients with MRI-confirmed partial-thickness and full-thickness RCT (PTRCT, FTRCT). We included patients who underwent initial course consisting of rest, activity modification, physical therapy, and/or injection for their condition. In our institution, all patients complete National Institutes of Health (NIH) Patient-Reported Outcomes Measurement Information System (PROMIS) assessments for physical function and pain interference. In patients with shoulder conditions, this consists of the PROMIS Upper Extremity Computer Adaptive Test (CAT) v2.0 ("PROMIS UE") and the PROMIS Pain Interference CAT v1.1 ("PROMIS PI"). Treatment modalities and follow-up PROMIS scores at least 6 weeks after initial visit were recorded. Using a distribution technique, the minimum clinically important difference (MCID) was calculated, and the proportion of patients achieving MCID for each tear group for both function and pain was determined. Chi-square tests were used to compare MCID achievement between PTRCT and FTRCT patients for both PROMIS UE and PROMIS PI. Results: A total of 100 FTRCT and 90 PTRCT patients were included in this analysis. Average age was 61.2 years, with 59% (n=112) female patients. The MCID for PROMIS UE was determined to be 3.9 and 3.9 for PTRCT and FTRCT patients, respectively. For PROMIS PI, MCID was 3.1 and 3.7 for PTRCT and FTRCT, respectively. In patients with PTRCT, the baseline score improved slightly from 31.4 to 34.9 for PROMIS UE, compared to a score change of 30.1 to 32.8 for patients with FTRCT. In total, 46% of PTRCT and 38% of FTRCT achieved MCID for PROMIS UE. In patients with PTRCT, the baseline score improved slightly from 63.1 to 60.0 for PROMIS PI, compared to a score change of 63.4 to 61.1 for patients with FTRCT. In total, 33% of PTRCT and 36% of FTRCT achieved MCID for PROMIS PI. When comparing PROMIS UE scores between PTRCT and FTRCT patients, there was no statistically significant difference in achievement of MCID (p=0.288). This was also the case for PROMIS PI (p=0.727). Conclusions: The present study identified MCID for PROMIS UE and PROMIS PI in both PTRCT and FTRCT undergoing conservative management. Only a minority of patients achieved MCID for pain (33% for PTRCT and 36% for FTRCT). A slightly higher proportion of patients achieved MCID for physical function (46% for PTRCT and 38% for FTRCT). The results of this study indicate that, while function may be more likely improved than pain, neither domains are significantly improved following initial nonoperative management in this patient population.